2009
DOI: 10.1016/j.jjcc.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mitral valvotomy versus closed surgical commissurotomy. Up to 15 years of follow-up of a prospective randomized study

Abstract: PMV achieves comparable results to CSC both in the short and long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
0
18
0
4
Order By: Relevance
“…Rifaie et al (15) showed that PMBV achieves comparable results to closed surgical commissurotomy both in the short and long-term. Careful patient selection, however, is necessary to achieve a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Rifaie et al (15) showed that PMBV achieves comparable results to closed surgical commissurotomy both in the short and long-term. Careful patient selection, however, is necessary to achieve a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Su efectividad, en cuanto a la magnitud de dilatación valvular, se correlaciona con el grado de alteración anatómica de la válvula 3 , y los resultados inmediatos son similares a los obtenidos con la comisurotomía quirúrgica cerrada 4 o abierta 5 , pero con menor morbilidad 6 . Del mismo modo, a mediano plazo existe evidencia de sus resultados favorables, con baja mortalidad y más de la mitad de los pacientes libres de eventos 7 .…”
unclassified
“…A técnica de balão único tem algumas vantagens em relação aos outros métodos de dilatação 14 : apresenta menor grau de dificuldade, pois a manipulação do cateter é mais fácil e seu uso não necessita guia; o risco de perfuração cardíaca também é menor; e, embora se obtenha área menor que a de duplo balão, a evolução clínica tardia de ambos os métodos é semelhante 15,16 . Neste estudo, o novo balão de dilatação demonstrou resultados superponíveis aos do balão clássico de Inoue, evidenciados pela similar taxa de sucesso e pelo baixo índice de complicações.…”
Section: Discussionunclassified